Meninjau Aspek Teknis Operasional UMKM “Angkringan Kampoeng Tua” Di Gresik - Sakha Windya Satria; Abdur Rahman (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This research is conducted to examine the phenomenon of the proliferation of micro, small, and medium-sized enterprises (MSMEs) in the form of “angkringan” businesses in Gresik, with a primary focus on the technical operational aspects in a feasibility study. The rapid growth of angkringan MSMEs in this region raises questions about the factors influencing the sustainability and success of these businesses. The aim of this research is to analyze various technical operational components, including operational management, efficiency, and business strategies applied by angkringan entrepreneurs. By employing qualitative and quantitative methods, this study is expected to provide in-depth insights into effective operational practices and offer strategic recommendations to enhance the competitiveness and sustainability of angkringan MSMEs in Gresik. The findings from this research are anticipated to serve as a valuable reference for business practitioners, policymakers, and academics interested in the development of culinary sector MSMEs.